Liver transaminase levels after intraportal autologous islet transplantation after partial pancreatectomy were associated with long-term metabolic outcomes - Ahn, Chang Ho; Jang, Jin-Young; Lee, Seong Ok; Yoon, Ji Won; Kim, Sun-Whe; Park, Kyong Soo; Jung, Hye Seung (Diabetes research and clinical practice, 2018)
To investigate the changes of post-procedural liver transaminase levels after autologous islet transplantation (ITx), and their associations with glycemic outcomes. Non-diabetic patients who underwent distal pancreatectomy for benign tumors were enrolled. Islets isolated from the healthy part of the resected pancreas were transplanted via the portal vein. Metabolic parameters were evaluated in the subjects for 5 years. Eight patients completed the study and four developed postoperative diabetes mellitus (PODM). Disposition index (DI) at postoperative 1 year showed prominent difference between the patients who develop PODM or not: DI was preserved in the PODM-free patients (49.7 ± 4.5 to 70.8 ± 14.4, P = 0.182), while it significantly decreased in the PODM patients (69.3 ± 9.9 to 28.5 ± 3.9, P = 0.019). The preoperative liver transaminase levels were not different between the two groups. However, transient increase in liver transaminase levels during the first week after ITx was observed only in the PODM patients, and their peak values demonstrated significant negative correlation with the changes in DI (r = −0.774 for alanine transaminase, r = −0.759 for aspartate transaminase; P < 0.05). Elevation of serum transaminases after ITx could be one of the factors determining insulin secretion and PODM.